The Future of ISIS Regional and International Implications - Ganguly, Sumit; al-Istrabadi, Feisal (Brookings Institution Press, 2018)
Looking to the future in confronting the Islamic StateThe Islamic State (best known in the West as ISIS or ISIL) has been active for less than a decade, but it has already been the subject of numerous histories and academic studies-all focus primarily on the past. The Future of ISIS is the first major study to look ahead: what are the prospects for the Islamic State in the near term, and what can the global community, including the United States, do to counter it?Edited by two distinguished scholars at Indiana University, the book examines how ISIS will affect not only the Middle East but the global order. The Future of ISIS is of interest to policymakers, analysts, and students of international affairs and public policy.